Taxonomic reconsideration of the subspecific complex of Laemostenus (Antisphodrus) cazorlensis (Mateu, 1953) (Coleoptera, Carabidae, Platyninae) - Muñoz-Santiago, José; Ortuño, Vicente M. (Zootaxa, 2020)
In this article we present a comparative study between the three subspecies of Laemostenus (Antisphodrus) cazorlensis (Mateu, 1953) (Coleoptera, Carabidae), a representative carabid of the cave fauna of Jaén and Albacete (southern Spain). The aim of this work was to examine the validity of the characters typically used to distinguish the subspecies L. (A.) c. cazorlensis (Mateu, 1953), L. (A.) c. divergens (Mateu, 1953) and L. (A.) c. seguranus (Vives & Vives, 1982) and check if they support the actual subspecific classification. For this purpose, a morphometric study of the pronotum and a morphological study of the male and female genitalia were carried out on 161 individuals of the three subspecies from the different geographic territories within the known distribution range of the species. An ANOVA analysis was run to support the results of the morphometric study developed with the total of studied samples. The results suggest that none of the studied characters can be used to characterize any of the subspecific taxa. Besides, the karstic profile of the ground in where this species inhabits could facilitate the genetic flow between its populations, so it is possible that they are not completely isolated. We conclude that the observable differences between individuals of Laemostenus (Antisphodrus) cazorlensis for the studied characters reflect intraspecific variability, and do not support a subspecific classification of the species. We propose the synonymization of the two non-typical subspecies of Laemostenus (Antisphodrus) cazorlensis with the typical one and, therefore, with the specific taxa.